Cryopreservation of spermatophores of the marine shrimp, Penaeus indicus H. Milne Edwards - Diwan, A D; Joseph, Shoji (Indian Journal of Fisheries, 2011)
Attempts on cryopreservation of spermatozoa have been made in penaeidshrimp, Penaeus indicus. Viable spermatozoa could be preserved successfullyfor a period of 60 days at -35Â°C and -196Â°C. Among several cryoprotectantsused, a combination of DMSO (5 %) and glycerol (5 %), DMSO (5 %) andtrehalose (0.25M) showed best viability rate (75 to 80 %) in freeze, thawedspermatozoa. Activational changes in spermatozoa during acrosome reactionafter induction with egg water have also been recorded. The importance ofcryogenic storage of spermatozoa is discussed